Tracing Lipid Metabolism by Alkyne Lipids and Mass Spectrometry: The State of the Art - Kuerschner, Lars; Thiele, Christoph (Frontiers in Molecular Biosciences, 2022)
Lipid tracing studies are a key method to gain a better understanding of the complex metabolic network lipids are involved in. In recent years alkyne lipid tracers and mass spectrometry have developed as a powerful tool for such studies. This text aims to review the current standing of the underlying technique, highlight major findings the strategy allowed for, summarize its advantages and discuss some limitations. Also an outlook on future developments is given.